KAJIAN HADITS TENTANG SILATURAHMI KEPADA TEMAN ORANG TUA YANG SUDAH MENINGGAL SEBAGAI SARANA PENDIDIKAN BAGI ANAK: Jurnal Ilmu Pendidikan - ridlwan, burhanuddin; Syamsuddin (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
This article discusses the hadith of silaturrahim to parents’ friends who have died as a means of educating children to be devoted to their parents. The hadith regarding the friendship of parents who have died as a means of educating children to serve their parents is based on the hadith that is contained in the book "al-Adab al-Mufrad" by Imam al-Bukhari. In essence, Islam requires Muslims to always respect their parents, cherish, say to their parents, say noble words, humble themselves to them, pray for them, then take care of their parents when they are old, and include hospitality with friends. Parents, all forms of filial piety to parents. stay in touch with friends of parents or close loved ones while still alive as a form of children's education to be devoted to our parents, education for ourselves when our parents have died.